Anticipating the more-than: Working with prehension in artful interventions with young people in a post-industrial community. (September 2019) - Renold, Emma; Ivinson, Gabrielle
Highlights: Anticipation framed within new feminist materialist ontologies of immanence can be explored as prehension (Manning 2013). Prehensions glimpsed in bodies and movements are explored with a speculative participatory arts-based praxis, developed over many years. Prehensions are transformed into creative artefacts with young people living in an ex-mining community experiencing post-industrial trauma. Artefacts materialise affective prehensions that signal the 'more than' of young people's beingness as a kind of unknown-known anticipation. Artefacts continue to vibrate as micro-political affective matter in the after life of a project that could not have been predicted in advance. Abstract: Inspired by speculative, post-qualitative research practices, this paper is framed within new feminist materialist ontologies of immanence to explore anticipation as the potentialities of the virtual, a prehension (Manning 2013) that can be glimpsed in bodies, movements and artful processes of creation. These 'prehensive' potentialities are explored with an arts-based praxis, developed over many years, with young people living in an ex-mining community experiencing post-industrial trauma to interrupt the sedimented practices that can lock some young people into feeling stuck and trapped. The paper follows a series of carefully composed events during a residential adventure weekend with a group of young people who wanted to explore their troubles by pushing their bodies to the limit with a range of physical activities and arts-based interventions. With 'art as the way' (Manning 2016), we map how our speculative praxis enabled us to attune to the embodied and embedded affects of young people's everyday practices, fears and concerns. We describe how prehensions as feelings, movements and images emerged and were transformed into creative artefacts; how these artefacts materialised affective prehensions as new and past potentials signalling the 'more than' of young people's beingness, as a kind of buried, unknown-known anticipation; and how the artefacts continue to vibrate as micro-political affective matter in the after life of a project that could not have been predicted in advance.